The perils of regulation and the theory of interventionism – an application to the Berlin rent freeze - Max Molden (The Review of Austrian Economics, 2023)
This paper studies the Berlin rent freeze introduced in 2020 and repealed in 2021. While the so-called Berliner Mietendeckel did lower rents in the regulated segment as intended, it was accompanied by several undesirable consequences, inter alia, less housing offered on the market. I take a dynamic, market process-based approach – relying on Kirzner's 'perils of regulation', and the theory of interventionism – in order to produce a comprehensive overview of the costs of the rent freeze which shall help inform a balanced judgment of the policy measure. Most significantly, the rent freeze impacted the discovery process: it stifled the systemic capacity to discover profit opportunities, and it created superfluous profit opportunities. While the types of these and similar costs can be described, the costs themselves are unknowable. Still, a comprehensive evaluation demands taking these costs into account. I conclude that the Berlin experience shows two things: Firstly, the aptness of a dynamic, market process-based approach to understand such phenomena, including explaining the rent freeze as part of a dynamic interventionist process. And second the superiority of the market process, the power of free entry, and the severity of knowledge problems for policy-makers.
Keywords: L50; P51; R38; 330; Interventions; Interventionism; Dynamics of the mixed economy; Price control; Rent policy